THE IMPLEMENTATION OF AUTHENTIC ASSESSMENT USING 2013 CURRICULUM - Amiza, Elsi (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
The purpose of this study is to describe the implementation of authentic assessment by theEnglish teachers using the 2013 English Curriculum. The description includes the types ofauthentic assessment used, the implementation and the problem faced by the teachers inimplementing the authentic assessment. The samples of the research were five Englishteachers and 34 students of grade X and XI in a senior high school in Padang Panjang.The data were collected through document analysis, questionnaire, and interview. Then,the data were analyzed descriptively. The result of the research shows that (1) the types ofauthentic assessment used by the five English teachers using the 2013 English Curriculumwere oral interview, observation, writing sample, project or exhibition, constructedresponditem, and performance-based assessment; (2) the implementation of authenticassessment is poor in the preparing, implementing in learning, scoring and reporting; (3)the problems faced are lack of time and knowledge about authentic assessment. It is,therefore, suggested that teachers are urged to improve their knowledge about authenticassessment by establishing training of implementing the authentic assessment at theschool.Keyword: Implementation, Authentic Assessment, 2013 Curriculum, English